A Tetrapositive Metal Ion in the Gas Phase: Thorium(IV) Coordinated by Neutral Tridentate Ligands1. Issue 27 (6th May 2013) - Gong, Yu; Hu, Han‐Shi; Tian, Guoxin; Rao, Linfeng; Li, Jun; Gibson, John K.
<x xml:space="preserve">Abstract</x> Sheltering thorium ions: A Th4+ ion supported by three neutral tetramethyl‐3‐oxaglutaramide ligands (L=TMOGA) is produced in the gas phase by electrospray ionization (see graph). The thorium in chiral Th(L)34+ is coordinated by nine oxygen atoms (see picture; O red, N blue, C gray). Quantum chemical studies revealed a decrease in ThO binding energies and bond orders and an increase in bond lengths, as the number of coordinating ligands increases.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>